Odpowiedzi

2009-09-24T18:33:12+02:00
A) 2x+1
b) 12x-2
c) 12a²-3
d) -56
e)16x
f)-6t+2
  • Użytkownik Zadane
2009-09-24T18:47:11+02:00
A)(x+1)²-2x²= x²+2x+1-2x²=-x²+2x+1
b)-2(3x-1)²+18²=-2(9x²-6x+1)+18²=-18x²+12x-2+324=-18x²+12x+322
c)3(2a+1)(2a-1)=3(4a²-2a+2a-1)=3(4a²-1)=12a²-3
d)(x+8)(x-8)-(x²-8)=x²-64-x²+8=-64+8=-56
e)-(x-4)²+(x+4)²=-(x²-8x+16)+(x²+8x+16)=-x²+8x-16+x²+8x+16=16x
f)(3t-1)²-(3t+1)(3t-1) =(3t²+6t+1)-(9t²-3t+3t-1)=3t²+6t+1-9t²+1=-6t²+6t+2
2009-09-24T18:53:20+02:00
A)(x+1)²-2x²=x²+2x+1-2x²=-x²+2x+1
b)-2(3x-1)²+18²=-2(9x²-6x+1)+324=-18x²+12x-2+324=-18x²+12x+322
c)3(2a+1)(2a-1)=3(4a²-1)=12a²-3
d)(x+8)(x-8)-(x²-8)=x²-64-x²+8=-56
e)-(x-4)²+(x+4)²=-x²+8x-16+x²+8x+16=16x
f)(3t-1)²-(3t+1)(3t-1)=9t²-6t+1-9t²-1=-6t